Prevalence of the Acute Respiratory Infections and Associated Factors in the Rural Areas and Urban Slum Areas of Western Maharashtra, India: A Community-Based Cross-Sectional Study - Murarkar, Sujata; Gothankar, Jayashree; Doke, Prakash; Dhumale, Girish; Pore, Prasad D.; Lalwani, Sanjay; Quraishi, Sanjay; Patil, Reshma S.; Waghachavare, Vivek; Dhobale, Randhir; Rasote, Kirti; Palkar, Sonali; et al. (Frontiers in Public Health, 2021)
Acute respiratory infections (ARIs) continue to be the most important cause of morbidity and mortality among under-five children. Some demographic and environmental factors are associated with ARIs among under-five children. This study was conducted with the objective to estimate the prevalence of ARIs among under-five children in the rural areas and densely populated urban slum areas in Maharashtra, India and to assess the association of the selected sociodemographic and household environmental factors with ARI. This study was conducted in 16 selected clusters from the rural areas and densely populated urban slum areas of the two districts in Maharashtra, India. Structured and validated proforma was used for collecting the data on the sociodemographic and household environmental risk factors. A total of 3,671 under-five children were surveyed. The prevalence of ARIs for the preceding month was 50.4%. It was higher among the children living in the rural areas (54.2%) compared to the children living in the urban areas (46.7%) (p = 0.01). The prevalence of ARIs was reported to be 51.4 and 49.4% in boys and girls, respectively. In the multivariate analysis, the researchers found that living in rural areas (p = 0.01) and parental smoking (p = 0.04) were significantly associated with the ARIs. An intervention such as reducing parental smoking habits at the household level may reduce ARIs.